2016
DOI: 10.1175/jpo-d-15-0245.1
|View full text |Cite
|
Sign up to set email alerts
|

Processes Associated with the Tropical Indian Ocean Subsurface Temperature Bias in a Coupled Model

Abstract: Subsurface temperature biases in coupled models can seriously impair their capability in generating skillful seasonal forecasts. The National Centers for Environmental Prediction (NCEP) Climate Forecast System, version 2 (CFSv2), coupled model, which is used for seasonal forecast in several countries including India, displays warm (cold) subsurface (surface) temperature bias in the tropical Indian Ocean (TIO), with deeper than observed mixed layer and thermocline. In the model, the maximum warm bias is reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…CFSv2 displays a too-weak stability for the upper 100 m as compared to WOA13, which is clearly seen in the bias (Figure 3d). The ERM profile is consistent with that for the entire tropical Indian Ocean (Chowdary et al, 2016b) and confirms the weak stability in CFSv2 (Figure 3b,e). Though upperocean salinity is better represented in MOM5 compared to CFSv2, the stability is still too weak in the top 60 m of the water column (Figure 3d,e).…”
Section: Inc-godas (Ocean Model Is Mom4)supporting
confidence: 82%
“…CFSv2 displays a too-weak stability for the upper 100 m as compared to WOA13, which is clearly seen in the bias (Figure 3d). The ERM profile is consistent with that for the entire tropical Indian Ocean (Chowdary et al, 2016b) and confirms the weak stability in CFSv2 (Figure 3b,e). Though upperocean salinity is better represented in MOM5 compared to CFSv2, the stability is still too weak in the top 60 m of the water column (Figure 3d,e).…”
Section: Inc-godas (Ocean Model Is Mom4)supporting
confidence: 82%
“…Recently, Chowdary et al . [] have demonstrated that upper ocean surface cooling in CFSv2 over tropical Indian Ocean is driven by the mixing.…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to note that the oceanic component (e.g., ocean heat transport and mixing) may also be responsible for SST differences. Recently, Chowdary et al [2016] have demonstrated that upper ocean surface cooling in CFSv2 over tropical Indian Ocean is driven by the mixing.…”
Section: Effects Of Cloud Microphysics On the Energy Budget At The Sumentioning
confidence: 99%
“…; Cai and Cowan, ; Chowdary et al . ). The interactions between the biases in the monsoon and the coupled air–sea interactions over the Indian Ocean remain part of the overall bias which cannot easily be untangled in a coupled system (Li et al .…”
Section: Resultsmentioning
confidence: 97%
“…Though CFS_NSS captures the monopole mode of variability, the variability explained by this mode is lower than the dipole mode (Figure 5c,f). This bias in models is quite common due to an excessive thermocline-mixed layer interaction in the eastern equatorial Indian Ocean, which results in a Bjerknes feedback and more frequent IOD events in contrast to the observed IOD (Annamalai et al, 2003;Cai and Cowan, 2013;Chowdary et al, 2016). The interactions between the biases in the monsoon and the coupled air-sea interactions over the Indian Ocean remain part of the overall bias which cannot easily be untangled in a coupled system (Li et al, 2015;Narapusetty et al, 2016;.…”
Section: Tropical Indian Oceanmentioning
confidence: 99%